GENETIC VARIABILITY, HERITABILITY AND GENETIC ADVANCE IN POINTED GOURD (Trichosanthes dioica Roxb.) (Bangladesh Journal of Plant Breeding and Genetics, 2007)
Genetic variability, heritability in broad sense and expected genetic advance as percent of mean for fruit yield and nine characters were studied in 25 pointed gourd genotypes. Fruits per plant and fruit yield per plant showed maximum variability. Genotypic coefficient of variation was found high for fruit yield and number of fruits per plant. All the characters under study were highly heritable in nature. High heritability coupled with high genetic advance was observed for fruit yield and fruits per plant, which indicated that these characters are more reliable for effective selection.DOI: http://dx.doi.org/10.3329/bjpbg.v20i1.17026